2016
DOI: 10.1371/journal.ppat.1006139
|View full text |Cite
|
Sign up to set email alerts
|

Fcγ-receptor IIa-mediated Src Signaling Pathway Is Essential for the Antibody-Dependent Enhancement of Ebola Virus Infection

Abstract: Antibody-dependent enhancement (ADE) of Ebola virus (EBOV) infection has been demonstrated in vitro, raising concerns about the detrimental potential of some anti-EBOV antibodies. ADE has been described for many viruses and mostly depends on the cross-linking of virus-antibody complexes to cell surface Fc receptors, leading to enhanced infection. However, little is known about the molecular mechanisms underlying this phenomenon. Here we show that Fcγ-receptor IIa (FcγRIIa)-mediated intracellular signaling thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 62 publications
(88 reference statements)
0
23
0
Order By: Relevance
“…For imaging of viral attachment and trafficking to late endosomes, VLPs consisting of the major EBOV structural proteins, GP, the matrix protein VP40, and nucleoprotein, were purified and DiI-labeled as described previously [ 9 ]. The HEK293 cells expressing enhanced green fluorescent protein fused to Rab7 (eGFP-Rab7), a late endosome marker was generated elsewhere [ 9 ]. HEK293 or HEK293 expressing eGFP-Rab7 cell lines were cultured in 35 mm glass-bottom dishes (MatTek Corporation) precoated with borate buffer containing 0.1 mg/ml poly-L-lysine (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For imaging of viral attachment and trafficking to late endosomes, VLPs consisting of the major EBOV structural proteins, GP, the matrix protein VP40, and nucleoprotein, were purified and DiI-labeled as described previously [ 9 ]. The HEK293 cells expressing enhanced green fluorescent protein fused to Rab7 (eGFP-Rab7), a late endosome marker was generated elsewhere [ 9 ]. HEK293 or HEK293 expressing eGFP-Rab7 cell lines were cultured in 35 mm glass-bottom dishes (MatTek Corporation) precoated with borate buffer containing 0.1 mg/ml poly-L-lysine (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Two distinct pathways of EBOV ADE are known; Fc receptor (FcR)-mediated and complement component C1q-mediated ADE [ 4 , 8 ]. We previously demonstrated that intracellular signaling pathways promoting phagocytosis and/or macropinocytosis play a key role in FcR-mediated ADE [ 9 ]. It is also known that the presentation of C1q induces enhanced phagocytic activity [ 10 ] and that C1q binds C1q receptors expressed on many different cell types and triggers signaling pathways such as Wnt/β-catenin, PI3K, and some tyrosine kinases [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mab 6D6 may, therefore, have potential as a therapeutic agent in animal models. He also described a novel antibody-dependent enhancement (ADE) mechanism in which Fc receptor-mediated intracellular signaling increased uptake of Ebola virus into cells in vitro (Furuyama et al, 2016). Activation of the Fc-receptor-mediated signaling pathway was essential for ADE of Ebola virus infection; this finding provides new insights into mechanisms of ADE and the development of treatments for ADE-associated diseases.…”
Section: Zoonosesmentioning
confidence: 99%
“…ADE of Ebola virus infection has been demonstrated in vitro in a variety of cell lines and is shown to be mediated by antibodies specific to the viral envelope glycoprotein (GP) (Takada et al 2001(Takada et al , 2007. Such enhancing antibodies have been identified in the sera of EVD patients Furuyama et al 2016). Two different mechanisms have been proposed for ADE of EBOV infection: (a) FcγR-mediated ADE and (b) C1q-mediated ADE.…”
Section: Ebola Virusmentioning
confidence: 99%
“…Two different mechanisms have been proposed for ADE of EBOV infection: (a) FcγR-mediated ADE and (b) C1q-mediated ADE. In FcγR-mediated ADE, antibody-virus complexes bind cell surface FcγRIIA triggering phosphorylation of Src family protein tyrosine kinases (PTKs) and activation of Src signaling pathways leading to virus uptake through phagocytosis and/or micropinocytosis (Furuyama et al 2016). C1q-mediated ADE involves interaction of virus-bound antibodies with complement component C1q and subsequent attachment to cell surface C1q receptors, leading to virus internalization by C1q receptor-mediated endocytosis or via virus-specific receptor (Takada et al , 2007.…”
Section: Ebola Virusmentioning
confidence: 99%